Regulated Forms of Cell Death in Fungi - Gonçalves, A. Pedro; Heller, Jens; Daskalov, Asen; Videira, Arnaldo; Glass, N. Louise (Frontiers in Microbiology, 2017)
Cell death occurs in all domains of live. While some cells die in an uncontrolled way due to exposure to external cues, other cells die in a regulated manner as part of a genetically encoded developmental program. Like other eukaryotic species, fungi undergo programmed cell death (PCD) in response to various triggers. For example, exposure to external stress conditions can activate PCD pathways in fungi. Calcium redistribution between the extracellular space, the cytoplasm and intracellular storage organelles appears to be pivotal for this kind of cell death. PCD is also part of the fungal life cycle, in which it occurs during sexual and asexual reproduction, aging, and as part of development associated with infection in phytopathogenic fungi. Additionally, a fungal non-self recognition mechanism termed heterokaryon incompatibility (HI) also involves PCD. Some of the molecular players mediating PCD during HI show remarkable similarities to major constituents involved in innate immunity in metazoans and plants. In this review we discuss recent research on fungal PCD mechanisms in comparison to more characterized mechanisms in metazoans. We highlight the role of PCD in fungi in response to exogenic compounds, fungal development and nonself recognition processes and discuss identified intracellular signaling pathways and molecules that regulate fungal PCD.